Rhabdomyolysis in a recreational swimmer. - Stella, J.J.; Shariff, A.H. (2012)
Rhabdomyolysis is a clinical and biochemical syndrome resulting from skeletal muscle injury, which may ultimately lead to acute renal failure (ARF) and death. Exertional rhabdomyolysis refers to skeletal muscle injury that is usually induced by strenuous eccentric exercises in a hot and humid environment. It is usually seen in marathoners and military personnel. We present the case of a 32-year-old Malaysian man who had rhabdomyolysis and myoglobinuria without ARF after two episodes of unaccustomed swimming. He was treated conservatively, and recovered uneventfully. A brief discussion on the pathophysiology of rhabdomyolysis, the principles of management and recuperation is included.